2017
DOI: 10.1080/14740338.2017.1376646
|View full text |Cite
|
Sign up to set email alerts
|

Safety issues associated with using medication to treat overactive bladder

Abstract: The mainstay of overactive bladder treatment is the use of anticholinergic medication with its common side effects well known. This review focused on three less well-known safety issues when treating OAB. Areas covered: Patients with increased anticholinergic load are at risk of cognitive decline, dementia or even death. The elderly are particularly at risk due to polypharmacy. Botulinum toxin carries the risk of high urinary residuals, urinary tract infection and need to self catheterise. The use of vaginal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Anticholinergic medications are commonly prescribed among older adults and are indicated for a range of conditions, including respiratory disease (asthma, chronic obstructive pulmonary disease), neurological/psychiatric conditions (depression, psychosis, Parkinson’s disease), gastrointestinal disorders, allergies, and overactive bladder (OAB) [ 1 3 ]. As many of these conditions increase in prevalence with age, it is unsurprising that up to half of older adults have been reported to have exposure to anticholinergic medications, sometimes multiple agents simultaneously [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticholinergic medications are commonly prescribed among older adults and are indicated for a range of conditions, including respiratory disease (asthma, chronic obstructive pulmonary disease), neurological/psychiatric conditions (depression, psychosis, Parkinson’s disease), gastrointestinal disorders, allergies, and overactive bladder (OAB) [ 1 3 ]. As many of these conditions increase in prevalence with age, it is unsurprising that up to half of older adults have been reported to have exposure to anticholinergic medications, sometimes multiple agents simultaneously [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anticholinergic medications have been associated with a variety of unwanted effects, including dry mouth, constipation, falls, and fractures, as well as neurological and behavioral issues such as delirium, cognitive impairment, and confusion [ 1 , 3 , 5 , 6 ]. Most recently, studies have found that exposure to certain anticholinergic medications, including some anti-depressants, bladder antimuscarinics, anti-epileptic drugs, and anti-Parkinson’s disease drugs, is associated with an increased risk of dementia, which is particularly concerning in an older population [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies report the impact of anticholinergics, largely used in overactive bladder, on the onset or increase of constipation. Several hypotheses are cited regarding the mechanisms of this iatrogenic effect: rectal contraction reduction, rectal impaired sensation 23 . The impact of increased retention with anticholinergic drugs in rectal sensation impairment can be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nested case-control study from general practices in England also concluded that exposure to higher total cumulative doses of anticholinergics was associated with increased risk of dementia in patients older than 55 years, especially in those who consumed more anticholinergic antidepressants, antiparkinson drugs, antipsychotics, bladder antimuscarinic drugs and antiepileptics [28]. Elderly patients using anticholinergics for overactive bladder have been found to have a higher incidence of dementia [29], especially when the anticholinergics have a small molecular size, a neutral charge, are lipophilic, are hydrophobic, and can cross the blood brain barrier easily [30]. The association between LUTS and increased dementia risk was demonstrated in our previous study [17], but the potential contributing factors remain unclear.…”
Section: Discussionmentioning
confidence: 99%